An Appraisal of Socio-Economic Factors Influencing GCE Ordinary Level Performance of Children belonging to the Peasant Community in Jaffna Peninsula - Umashankar, L. (Faculty of Agriculture, University of Jaffna, Sri Lanka, 2017)
Agriculture is the mainstay of a significant section of the populace in the Jaffna peninsula. Consequently, any progress in the welfare in the lives of those involved in agriculture, certainly would result in the progress of the entire region. Education is an essential element in the sustainable development goals of the United Nations (UNSDG 4). The most recent media reports seem to reveal that performance of the Jaffna district at GCE (O/L) falls behind the rest of the districts of Sri Lanka. Thus, researcher has endeavoured to identify the causes which led to such a result. To this end, 312 students were selected by a purposive random sampling procedure from all nine educational zones in the Jaffna district. A pretested structured questionnaire was administered to the students selected during the period of April to May, 2017. A multiple regression analysis was performed by employing the econometric software STATA 13. The results revealed that, self-study of each pupil had contributed positively in the elevation of performance in all subjects at 1% probability level. This implies that when the students' individual average studying time increases by one-time unit the average marks scored increased by 6.69, 5.92, and 5.21 units in mathematics, science, and Tamil respectively. It reveals that, besides, their application at home, enhances their overall performance considerably. However, no significant relationship is indicated in the performance of a pupil in respect to the number of hours spent in tuition. It is also seen that the attitude of the parents, due to their shortfall in education, which makes them believe that school hours and tuition hours together, will suffice to help their children succeed, is false. Besides, the visits to the library affect positively at 5% significant level, the cumulative average marks of the students in science and Tamil Language. It is recommended that adequate facilities be provided for children in peasant families and they be encouraged to visit libraries. Besides, with reference to their children's education an awareness extension program is recommended to target peasant parents. Those NGOs or any philanthropists or Governmental organisations dealing with the wellbeing of peasants, if they institute self-study units in homes for children, it would be very effective in enhancing performance and the same is recommended strongly.
Keywords: Jaffna peninsula; Peasant students; Education performance; Awareness extension program